Eleven-Year Trends in Lipid-Modifying Medicines Utilisation and Expenditure in a Low-Income Country: A Study from the Republic of Srpska, Bosnia and Herzegovina - Kalinić D; Škrbić R; Vulić D; Stoisavljević-Šatara S; Stojaković N; Stojiljković MP; Marković-Peković V; Golić Jelić A; Pilipović-Broćeta N; Divac N (Dove Medical Press, 2023)
Dragan Kalinić,1 Ranko Škrbić,2 Duško Vulić,3 Svjetlana Stoisavljević-Šatara,2 Nataša Stojaković,2 Miloš P Stojiljković,2 Vanda Marković-Peković,4 Ana Golić Jelić,4 Nataša Pilipović-Broćeta,5 Nevena Divac6 1Centre for Biomedical Research, Faculty of Medicine, University of Banja Luka, Banja Luka, 78000, Republic of Srpska, Bosnia and Herzegovina; 2Department of Pharmacology, Toxicology and Clinical Pharmacology, Faculty of Medicine, University of Banja Luka, Banja Luka, 78000, Republic of Srpska, Bosnia and Herzegovina; 3Centre for Specialisations and Continuous Medical Education, Faculty of Medicine, University of Banja Luka, Banja Luka, 78000, Republic of Srpska, Bosnia and Herzegovina; 4Department of Pharmacy, Faculty of Medicine, University of Banja Luka, Banja Luka, 78000, Republic of Srpska, Bosnia and Herzegovina; 5Family Medicine Teaching Centre, Primary Healthcare Centre of Banja Luka, Banja Luka, 78000, Republic of Srpska, Bosnia and Herzegovina; 6Department of Pharmacology, Clinical Pharmacology and Toxicology, Faculty of Medicine, University of Belgrade, Belgrade, 11000, SerbiaCorrespondence: Dragan Kalinić, Centre for Biomedical Research, Faculty of Medicine, University of Banja Luka, Save Mrkalja 14, Banja Luka, 78000, Republic of Srpska, Bosnia and Herzegovina, Tel/Fax +387 51 234 101, Email dragan.kalinic@med.unibl.orgBackground: In last two decades, there have been substantial changes in the pattern of lipid-modifying medicines utilisation following the new treatment guidelines based on clinical trials. The main purpose of this study was to analyse the overall utilisation and expenditure of lipid-modifying medicines in the Republic of Srpska, Bosnia and Herzegovina during an 11-year follow-up period and to express its share in relation to the total cardiovascular medicines (C group) utilisation.Methods: In this retrospective, observational study, medicines utilisation data were analysed between 2010 and 2020 period using the ATC/DDD methodology and expressed as the number of DDD/1000 inhabitants/day (DDD/TID). The medicines expenditure analysis was used to estimate the annual expenditure of medicines in Euro based on DDD.Results: During the analysed period, the use of lipid-modifying medicines increased almost 3-times (12.82 DDD/TID in 2010 vs 34.32 DDD/TID in 2020), with a rise in expenditure from 1.24 million Euro to 2.15 million Euro in the same period. This was mainly driven by an increased use of statins with 163.07%, and among these, rosuvastatin increased more than 1500-fold, and atorvastatin with 106.95% increase. With the appearance of generics, simvastatin showed a constant decline, while the other lipid-modifying medicines in relation to the total utilisation had a neglecting increase.Conclusion: The use of lipid-modifying medicines in the Republic of Srpska has constantly increased and strongly corresponded to the adopted treatment guidelines and the positive medicines list of health insurance fund. The results and trends are comparable with other countries, but still the utilisation of lipid-lowering medicines represents the smallest share of total medicines use for the treatment of cardiovascular diseases, compared to high-income countries.Keywords: lipid-modifying medicines, medicines utilisation, ATC/DDD methodology, medicines expenditure, medicines positive list